GAMBARAN PENGETAHUAN IBU RUMAH TANGGA TERHADAP DAGUSIBU OBAT DI DUSUN SALO, DUA DESA SALO DUA, KECAMATAN MAIW, KABUPATEN ENREKANG TAHUN 2025 - Sabila, Nur Zal (Jurnal Penelitian Farmasi Dan Herbal, 2025)
This study aims to determine the level of knowledge among housewives regarding DAGUSIBU (Obtaining, Using, Storing, and Disposing of Medicines) in Dusun Salo Dua, Enrekang Regency, and to identify which components of DAGUSIBU are well understood or need further improvement. This research used a descriptive quantitative method involving 67 respondents selected through purposive sampling based on specific inclusion criteria. Data were collected using a validated and reliable questionnaire and analyzed using univariate descriptive statistics. The results showed that 70.15% of respondents had good knowledge, while 29.85% had sufficient knowledge of DAGUSIBU. Component-wise, knowledge about “obtaining” medicines was relatively low (66.67%), while “using” (79.85%), “storing” (89.05%), and “disposing” (83.6%) were classified as good. Higher knowledge was associated with age over 35 and higher education levels. However, many respondents still acquired medicines from unofficial sources, indicating the need for more targeted health education. This finding emphasizes the importance of strengthening public knowledge and behavior regarding medicine use. Future interventions should include structured community outreach and collaboration with healthcare providers. Moreover, qualitative studies are recommended to explore underlying factors affecting household medicine management and to support the rational use of medicines at the community level.